The Relationship Between Self-Stigma and Negative Social Perceptions on the Intention to Seek Professional Psychological Help Among Young Adults in Bandung - Adhistyrizkika Kurnia Putri; Rifqi Farisan Akbar; Prinska Damara Sastri (International Journal of Marketing & Human Resource Research, 2026)
This study aims to examine the relationships between self-stigma, perceived social negativity, and the intention to seek professional psychological help among emerging adults in Bandung City. A total of 100 participants were selected using a non-probability purposive sampling technique, with the sample size determined using the Slovin formula (10% margin of error). Data were collected using standardized questionnaires measuring self-stigma, perceived social negativity, and help-seeking intention, aafter all statistical assumptions had been met. The findings indicate that self-stigma and perceived social negativity are significantly associated with the intention to seek professional psychological help among emerging adults in Bandung. Perceived social negativity showed a stronger relationship with help-seeking intention than self-stigma. Together, both variables substantially contributed to explaining variations in help-seeking intention. Because the help-seeking intention scale was reverse-scored, higher scores indicated a lower intention to seek professional psychological help. These findings suggest that both psychological and social factors play an important role in shaping emerging adults intention to seek professional psychological help. Therefore, the study highlights the importance of stigma reduction and mental health literacy initiatives to encourage greater willingness to seek professional help